Bilingual Students' Experience in Learning English - Munawaroh, Munawaroh (Universitas Jambi, Magister Program of English Education Department, 2022)
The research aimed to investigate the bilingual students’ experience in learning English. The method chosen is phenomenological research. The researcher collected the data trough interview. The finding of the research found in this research are: the students’ started to go to international school from toddler, nursery, kindergarten or even primary school, the students able to speak English well because of the school environment demanded them to speak English; not only at school the students also improve their English by joining in English private tutorial; and the last, the students acquired the second language by some platform such as English movie, YouTube, online game.